Association between human papillomavirus (HPV) and the oral squamous cell carcinoma: A systematic review - De Lima, Marcos Antonio Pereira (2014)
The human papillomavirus (HPV) is an epitheliotropic agent whose high-risk genotypes have a well-established link with the development of cervical cancer. Although the relation of HPV to the oral squamous cell carcinoma (OSCC) has been studied since the beginning of the 1980s, its role in the oral carcinogenesis and the probable underlying molecular mechanisms are still not fully elucidated. We performed a systematic review of the worldwide scientific literature, published until the preparation of the present paper, concerning the association of HPV with OSCC, scrutinizing the samples, prevalence levels, the techniques utilized and relevant findings of the studies. The results showed that HPV is associated with approximately one quarter of OSCCs. Another interesting feature is the distinct pattern of infection in these oral tumors, including the participation of genotypes that are uncommon in cervical malignant lesions, such as HPV-38, 44, 53 and 70. Equally interesting is the possibility of carcinogenic action without the occurrence of viral integration, verified by the high expression of messenger ribonucleic acid (mRNA) of E6 and E7 from high-risk genotypes in cases whose virus remain in the episomal form. These findings support the assumption of HPV involvement in the genesis of OSCC, whereas warn about the possibility of unexpected viral behaviors that sometimes are not perceived or understood due to the technological limitations of the time and to the shortage of studies with the adequate approaches.